The importance of egg size for the diversity of salmonids - Leblanc, Camille A. 1981- (2011)
Drg. frá Háskóla Íslands og Oregon State University, 2011 Salmonids display great diversity in terms of behaviour, life histories and morphology within and among populations. Such diversity results from a combination of genetic, environmental and ecological factors. Here I studied the short- and long-term effects of egg size on development, behaviour, growth and physiology in Arctic charr Salvelinus alpinus and steelhead trout Oncorhynchus mykiss (wild and domesticated). In both species, egg size was smaller in domesticated populations. Egg size was negatively correlated with embryonic development. Larger eggs contained more energy in both aquaculture and wild populations of Arctic charr. Egg size related to behaviour of juveniles of both species, juveniles coming from larger eggs tended to feed more at the surface whereas juveniles coming from smaller eggs fed more on the bottom. After several months of rearing we found that the influence of egg size on behaviour and morphology of Arctic charr varied with female parentage, indicating strong maternal x genetic interactions. In steelhead trout, both origin of fish and egg size were related with growth of yearling fish reared under laboratory conditions. The results of this are new and show that variation in egg size is crucial for phenotypic variability. My results support the hypothesis that females who grow relatively rapidly as juveniles produce a large number of small eggs as adults. Thus, changes in egg size occur rapidly (in only one domesticated generation). Finally, I discuss the implications of egg size for evolution and how diversity created by egg size can influence diversification and speciation of fishes. Hjá laxfiskum má finna mikinn fjölbreytileika, innan og milli stofa, í atferli, lífssögu og svipfari. Þessi fjölbreytni hefur orðið til vegna samspils erfða-, umhverfis – og vistfræðilegra þátta. Ég rannsakaði bæði skammtíma og langtíma áhrif hrognastærðar á þroska, atferli og lífeðlisfræði bleikju Salvelinus alpinus og regnbogasilungs ...